A study on the insecticidal property of the leaves of flame tree (Caesalpinia Pulcherrima (L.) Sw.) - Alcantara, Jocelyn Pablo (Animo Repository, 1984)
The insecticidal activity of the crude extracts prepared by successive extraction of the leaves of flame tree (Caesalpinia pulcherrima (L.) Sw.) in petroleum ether, acetone, methanol, and water was tested on cockroaches. Of the four crude extracts tested, petroleum ether, methanol, and acetone crude extracts were found to have considerable insecticidal properties. The petroleum ether crude extract was found to be the most toxic on cockroaches and was subsequently analyzed to isolate the insecticidal fractions which may be responsible for the activity. The interphase extractions of the organic components in the petroleum ether crude extract after chlorophyll was precipitated were done using two solvents petroleum ether and chloroform. The resulting semi-purified extracts were still toxic when tested on cockroaches. Partial isolation of the components of the semi-purified extract from petroleum ether was attained by flash chromatography. The components of the semi-purified extract from chloroform were isolated by column chromatography and were labeled as Fraction A, B, C, and D. Toxicity test result of the fraction showed that Fraction C gave the highest percentage mortality. Preliminary characterization of Fraction C by NMR spectroscopy indicated the presence of hydrocarbons, i.e. -CH2 and -CH3 groups as shown by the peaks at high field, atLof around 0.90 ppm.